Theoretical and Experimental Investigations of Peculiar Features in Micro-Structure Formation and Phase Composition of Hydrogen-Resistant Coatings of Self-Fluxing Alloys and Compositions on Their Basis - A. F. Prisevok; G. Ya. Beliaev; V. A. Smiotkin; A. B. Pankov; T. E. Opekounova (Наука и техника)
The paper presents results of theoretical and experimental investigations of peculiar features in formation of micro-structure and phase composition of protective (hydrogen-resistant) coatings of self-fluxing alloys and compositions on their basis at surface (high frequency current), solid (in a furnace) and laser flashings.